THE PECULIARITIES OF THE U. S. HIGHER EDUCATION DEVELOPMENT STRATEGY IN THE CONTEXT OF CURRENT CONDITIONS - Olga I. Fomina (Образование и наука)
Abstract. The aim of the research is to investigate a current state of the US higher education and to show obstacles in a way of its innovative perfection; to reveal specificity of the US state policy concerning the higher school; to define factors that influence the effectiveness of the American research universities during the last decades. Methods. The author applies for methods of the retrospective and logic analysis while considering social and economic conditions and features of functioning of the American higher educational institutions during the latter half of 20th – the early 21st centuries. Conclusions on a condition and prospects of development of the US higher education are made on the basis of the review and the author’s interpretation of original documentary sources tenor and the official statistical data. Results. The author specifies the groups of factors that provide functioning efficiency of leading research universities of the USA. The research findings demonstrate that the diversification of funding sources, the concentration of talents in professorial, scientific, student communities, the guarantee of the academic mobility, and the favorable management structure of the US universities allow to lower dependence on economic instability, to provide development dynamism and adequately react to present calls. The characteristic of the system developed in the present period of the US higher education is given; the directions of its innovative development in modern conditions are defined. Scientific novelty. The author singles out and proves the problems of the US higher school caused by an economic crisis in the early 21st century and essentially affected the state strategy in educational management sphere and the corporate policy of high schools, taking into consideration the inescapable fact that features of the US higher education system are caused by aspiration of this state to hold the leading positions in the world community. The contradictions of innovative development of higher education of the USA are revealed. The author notes that universities raise a student fee focusing on well-off students in an effort to stabilize its financial position forces as it negatively affects the formation of an intellectual potential of the country. On the one hand, accessibility (massification) of higher education due to distant technologies provides international popularity to the US universities; on the other hand, it lowers the education quality. Practical significance. Implementation of the research outcomes while studying the positive foreign experience and judgements of the American colleagues in strategy of management adoption and the higher school organisation will help the Russian ones to find own way of rational and effective modernization of vocational training.